(untitled) (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2025)
This study examines mortality patterns among different age groups of older persons in Nepal, where 15% of the population was aged 65 or older in 2021. Using data from the Nepal Population and Housing Census (NPHC) 2021, the research analyzes lifespan, aging patterns, disability prevalence, and causes of death across all ages. Findings reveal a demographic shift from 5.0% of people aged 65+ in 1952/54 to 10.2% in 2021. Life expectancy increased to 68.8 years for women and 28.5 years for men. Disability affected 6.9% of seniors, with physical health and vision problems being most common, and a higher prevalence in men. Non-communicable diseases (NCDs) caused 61.7% of deaths in the 65–69 age group, while communicable diseases and natural disasters accounted for 10.5% and 5.4%, respectively. Among those over 80, 38.3% of deaths had unclear causes. The findings underscore increasing NCDs, disabilities, and environmental challenges among Nepal’s elderly, highlighting the need for enhanced geriatric care, gender-sensitive policies, and improved vital records. The study advocates for longitudinal research and regional analysis to inform effective aging-related policy interventions.